Pengaruh Kombinasi Ekstrak Daun Kelor (Moringa Oleifera L.) dan Daun Kirinyuh (Chromolaena Odorata L.) terhadap Daya Hambat Pertumbuhan Bakteri Salmonella Typhi ATCC 14028: Penelitian - Putri Nur Arlin; Sonja Verra Tinneke Lumowa; Sri Purwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Salmonella typhi causes typhus, which continues to be a health challenge in various countries. One alternative to inhibit bacterial growth is to use antibacterial compounds from plants. Leaves of moringa (Moringa oleifera L.) and kirinyuh (Chromolaena odorata L.) have secondary metabolites that are known to have antibacterial properties. Determining the secondary metabolite composition of the two leaf types and evaluating the impact of extract combination on Salmonella typhi inhibition are the goals of this study. An experimental approach employing This investigation was carried out utilizing a completely randomized design (CRD), which included five different extract concentrations that were examined using the well diffusion method, a negative control, and a positive control (chloramphenicol). The outcome of phytochemical analysis show that both leaves contain alkaloids, phenolics, tannins flavonoids, steroids and saponins. However, the inhibition test showed that neither the single extract nor the combination of Moringa and kirinyuh leaves formed a clear inhibition zone, whereas the chloramphenicol used as a control was 28.9 mm. Thus, moringa and kirinyuh leaf extracts did not show antibacterial activity against Salmonella typhi. However, chloramphenicol proved successful in preventing these germs from growing.